Advanced introduction to international human rights law - Shelton, Dinah (Cheltenham, UK : Edward Elgar, 2014)
This text provides a concise and lucid account of this field of International law, from a leading authority on the subject.
Includes bibliographical references (pages 297-302) and index.
Keywords: Human rights